Epstein-Barr virus-associated smooth muscle tumour: two case reports - Hussin, Huzlinda; Abdul Kahar, Nor Farahin; Mohd Dusa, Noraini; Abd Rani, Nor Haizura (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Epstein-Barr virus-associated smooth muscle tumour (EBV-SMT) is an intermediate mesenchymal neoplasm recognised in immunocompromised patients, including HIV-infected patients. EBV-SMT is challenging to diagnose since it occurs in various age groups and anatomical sites and presents with nonspecific symptoms. The diagnosis is further complicated by the similarity of its histopathological features with other spindle cell tumours. A clinical history of immunosuppression, immunohistochemistry study and association with Epstein-Barr. virus (EBV) infection can aid in the diagnosis. Here, we reported two cases of EBV-SMT in two patients with HIV infection, emphasising the histomorphology features and immunohistochemical profile that help in the diagnosis.